Perlindungan Hukum Bagi Pekerja yang Dirumahkan Akibat Pandemi Covid-19 - Ananda Chrismond Endika Putra (Jurist-Diction, 2021)
AbstractThe problem that becomes an obstacle is the imbalance of employment opportunities for workers, welfare and protection of workers. Problems related to the welfare and protection of workers include the minimum wage that is still needed. Currently the Covid-19 Pandemic has had quite a number of workers who have changed their habit of office activities by working at home or at home. During the Covid-19 pandemic, workers or workers have the right to protection for safety and health in doing work. Protection of workers can be carried out, by providing guidance, as well as by increasing recognition of human rights, physical protection and technical, social and economic protection. There are special rules regarding home workers in the Circular of the Minister of Manpower Number: SE-05 / M / BW / 1998 concerning Wages for Home Workers not towards termination of the relationship but the company still pays the full wage and can regulate but is obliged to negotiate with the union laborers / workers. Disputes over employee relations with the company can go wrong through the non-litigation and litigation channels.Keywords: Protection; Wages; Settlement.AbstrakDalam masalah yang menjadi hambatan yaitu tidak seimbangnya kesempatan kerja bagi pekerja, kesejahteraan dan perlindungan terhadap pekerja. Terkait permasalahan dalam kesejahteraan dan perlindungan terhadap pekerja antara lain upah minimum yang masih dibawah kebutuhan. Saat ini Pandemi Covid-19 cukup banyak para pekerja yang mengganti kebiasaan kegiatan ke kantor dengan bekerja di rumah atau dirumahkan. Saat pandemi covid-19 ini para pekerja ataupun buruh berhak mendapatkan perlindungan atas keselamatan dan kesehatan dalam melakukan pekerjaan. Perlindungan pekerja dapat dilakukan, dengan memberikan tuntunan, maupun dengan meningkatkan pengakuan hak-hak asasi manusia, perlindungan fisik dan perlindungan teknis sosial dan ekonomi. Terdapat Aturan khusus mengenai pekerja yang di rumahkan pada Surat Edaran Menteri Tenaga Kerja Nomor: SE-05/M/BW/1998 tentang Upah Pekerja yang Dirumahkan bukan kearah pemutusan hubungan namun perusahaan tetap membayar upah secara penuh dan dapat dikurangi namun wajib melakukan perundingan dengan serikat buruh/pekerja. Persoalan perselisihan hubungan pekerja dengan perusahaan dapat diselesaikan melalui jalur non-litigasi dan jalur litigasi. Kata Kunci: Perlindungan; Pengupahan; Penyelesaian.